Charge detection mass spectrometry on human-amplified fibrils from different synucleinopathies. Issue 51 (7th June 2022) - Tsirkou, Aikaterini; Kaczorowski, Flora; Verdurand, Mathieu; Raffoul, Rana; Pansieri, Jonathan; Quadrio, Isabelle; Chauveau, Fabien; Antoine, Rodolphe
Abstract : Nanospray-charge detection mass spectrometry was performed on α-synuclein fibrils amplified from human brains and demonstrated its synergistic combination with real-time quaking-induced conversion to characterize amyloid deposits in neuropathology. Abstract : Amyloid fibrils are self-assembled mesoscopic protein aggregates, which can accumulate to form deposits or plaques in the brain. In vitro amplification of fibrils can be achieved with real-time quaking-induced conversion (RT-QuIC). However, this emerging technique would benefit from a complementary method to assess structural properties of the amplification products. This work demonstrates the feasibility of nanospray-charge-detection-mass-spectrometry (CDMS) performed on α-synuclein (αSyn) fibrils amplified from human brains with Parkinson's disease (PD) or Dementia with Lewy bodies (DLB) and its synergistic combination with RT-QuIC.